Genomic Landscape and Potential Regulation of RNA Editing in Drug Resistance - Xu Zhou; Ramkrishna Mitra; Fei Hou; Shunheng Zhou; Lihong Wang; Wei Jiang (Advanced Science)
Abstract Adenosine‐to‐inosine RNA editing critically affects the response of cancer therapies. However, comprehensive identification of drug resistance‐related RNA editing events and systematic understanding of how RNA editing mediates anticancer drug resistance remain unclear. Here, 7157 differential editing sites (DESs) are identified from 98 127 informative RNA editing sites in tumor tissues, many of which are validated in cancer cell lines. Diverse editing patterns of DESs are discovered in resistant samples, which could not be fully explained by adenosine deaminase acting on RNA enzymes. Some RNA‐binding proteins are identified that potentially regulate these editing events. Notably, the DESs are significantly enriched in 3’‐untranslated regions (3’‐UTRs). The impact of DESs in 3’‐UTR on the microRNA (miRNA) regulations is explored, and some triplets (DES, miRNA, and gene) that may contribute to drug resistance are identified. In addition, it is determined that the functions of genes enriched with DESs are associated with drug resistance, such as apoptosis, drug metabolism, and DNA synthesis involved in DNA repair. An online resource (http://www.jianglab.cn/REDR/) to support convenient retrieval of DESs is also built. The findings reveal the landscape and potential regulatory mechanism of RNA editing in drug resistance, providing new therapeutic targets for reversing drug resistance.